Chonewood: una historia paralela del cine ecuatoriano - Reyes, Luis Stéfano Murillo (2020)
This research investigates the cinema made in the city of Chone located on the Ecuadorian coast. Here Since 1994 there has been a phenomenon within Ecuador's cinema historically marked by a discontinuity. This phenomenon is called Chonewood that was born at first as the need to tell stories by filmmakers of Chone, influenced by foreign cinema that arrived in the cinemas of the region and mainly by the violent environment of the city. At first, a historical picture of the history of centralized Ecuadorian cinema is realized in the country's great cities, Quito and Guayaquil, in order to understand the discontinuities in production and, on the other hand, part at various times, the State as participate in supporting domestic production. Then, the Chonewood cinema, the filmmakers' journey, the processes established, the circulation and distribution in the informal market of their films, and the encounters with the state and the academy are then studied.